2018
DOI: 10.3168/jds.2018-14395
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chlorine ions in raw milk by pulsed amperometric detection in a flow injection system

Abstract: Chloride ion concentration in milk was determined by pulsed amperometric detection in a flow injection system. Results showed that the Au electrode lost 3 electrons at 1.10 V and formed chloroaurate ions (AuCl) by combining with chloride ions, after which AuCl was partly reduced to Au at 0.6 V. Based on the electrochemical process, a triple waveform with detection potential of 1.15 V, detection time of 150 ms, oxidation potential of 1.4 V, oxidation time of 550 ms, reduction potential of 0 V, and reduction tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Meanwhile, the redox peak current of [Fe(CN) 6 ] 3−/4− on β-GCNT increased significantly as the scanning rate increased and featured a good linear relationship with the square root of the scanning rate (Figure 1J,K). These findings demonstrated that the composites composed of β-CD and MWCNT could efficiently promote electron transfer with a diffusion-controlled process [10]. It was worth noting that the peak current of β-GCNT was obviously enhanced in comparison to GCNT and the peak current of β-GCE showed little increase in comparison to GCE.…”
Section: Electrochemical Characterizationmentioning
confidence: 78%
See 4 more Smart Citations
“…Meanwhile, the redox peak current of [Fe(CN) 6 ] 3−/4− on β-GCNT increased significantly as the scanning rate increased and featured a good linear relationship with the square root of the scanning rate (Figure 1J,K). These findings demonstrated that the composites composed of β-CD and MWCNT could efficiently promote electron transfer with a diffusion-controlled process [10]. It was worth noting that the peak current of β-GCNT was obviously enhanced in comparison to GCNT and the peak current of β-GCE showed little increase in comparison to GCE.…”
Section: Electrochemical Characterizationmentioning
confidence: 78%
“…470 mV were controlled by diffusion [31]. Meanwhile, the electron transfer number of the above reversible peak was calculated to be about two, according to Laviron's theory [10,33]. Figure 2C illustrated the CV curves of capsaicin under different pH values.…”
Section: The Electrochemical Reaction Process Of Capsaicinmentioning
confidence: 98%
See 3 more Smart Citations